2018
DOI: 10.2147/ijn.s179484
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticle-conjugated nutraceuticals exert prospectively palliative of amyloid aggregation

Abstract: Alzheimer’s disease (AD), an age-related neurodegenerative disease, the most common causes of dementia is a multifactorial pathology categorized by a complex etiology. Numerous nutraceuticals have been clinically evaluated, but some of the trials failed. However, natural compounds have some limitations due to their poor bioavailability, ineffective capability to cross the blood–brain barrier, or less therapeutic effects on AD. To overcome these disadvantages, nanoparticle-conjugated natural products could prom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 141 publications
0
8
0
Order By: Relevance
“…Resveratrol showed antioxidant activity and anti-Aβ formation features both in vivo , in Tg2576 mice, and in vitro through different molecular mechanisms, including inhibition of β-amyloid-induced neuronal apoptosis via regulation of the silent information regulator 1 (SIRT1)-Rho-associated kinase 1 (ROCK1) signaling pathway in PC12 cells and by promoting non-amyloidogenic processing of APP, and thus mitigating Aβ neuropathology in AD ( Wang et al, 2006 ; Ladiwala et al, 2010 ; Feng et al, 2013 ). However, recent AD clinical trials with natural compounds, including curcumin and resveratrol as well, failed in different phases to successfully treat AD ( Kanubaddi et al, 2018 ). This has been partially due to the low aqueous solubility, poor bioavailability, and ineffectiveness against the disease mainly because of the low penetration of resveratrol and other natural molecules across the BBB; whereby the need of alternative NP-based formulations for improving pharmacokinetic properties, bioavailability, neural targetability and the great clinical potential of these nutraceuticals ( Summerlin et al, 2015 ; Kanubaddi et al, 2018 ).…”
Section: Preclinical Achievements Of Polymeric Nanoparticles-mediated...mentioning
confidence: 99%
“…Resveratrol showed antioxidant activity and anti-Aβ formation features both in vivo , in Tg2576 mice, and in vitro through different molecular mechanisms, including inhibition of β-amyloid-induced neuronal apoptosis via regulation of the silent information regulator 1 (SIRT1)-Rho-associated kinase 1 (ROCK1) signaling pathway in PC12 cells and by promoting non-amyloidogenic processing of APP, and thus mitigating Aβ neuropathology in AD ( Wang et al, 2006 ; Ladiwala et al, 2010 ; Feng et al, 2013 ). However, recent AD clinical trials with natural compounds, including curcumin and resveratrol as well, failed in different phases to successfully treat AD ( Kanubaddi et al, 2018 ). This has been partially due to the low aqueous solubility, poor bioavailability, and ineffectiveness against the disease mainly because of the low penetration of resveratrol and other natural molecules across the BBB; whereby the need of alternative NP-based formulations for improving pharmacokinetic properties, bioavailability, neural targetability and the great clinical potential of these nutraceuticals ( Summerlin et al, 2015 ; Kanubaddi et al, 2018 ).…”
Section: Preclinical Achievements Of Polymeric Nanoparticles-mediated...mentioning
confidence: 99%
“…It was demonstrated that resveratrol is efficient in the attenuation of neuronal injuries and the modulation of neuronal signaling and glial pathways, as well as in the autophagy process [ 7 ]. Furthermore, resveratrol nanocarriers obtained by encapsulating or conjugating it in SLNs or nanocapsules, have shown improved solubility and a slower metabolism associated with their capability to efficiently target and inhibit the formation/aggregation of Aβ peptides [ 59 ]. Kanubaddi and colleagues reported improvements in the stability and solubility (dependent on the hydrophobic nature) of curcumin, a turmeric derivative belonging to the ginger family, which can bind to and dissolve Aβ aggregates when conjugated with AuNPs, nanogels, polymeric NPs, and nanoliposomes [ 59 ].…”
Section: Nutraceutical-loaded Nps and Green Npsmentioning
confidence: 99%
“…Today (April, 14 th 2020) in PUBMED database, a search through the keywords "nutraceutical" and "Alzheimer" retrieves more than 200 papers in a limited selection to the last five years, but only 1 (a review) if the keyword "nanomedicine" or "nanoparticle" was added. 85 This indicates that a comprehensive revision of the literature in this field is lacking and that dedicated reviews may be needed. Here, only the more recent advances in this field are indicated ( Table 2).…”
Section: Nutraceutical Loaded Nps and Green Npsmentioning
confidence: 99%
“…Data showed how resveratrol could reach the brain and inhibit the formation and aggregation of Aβ peptides. 8,85 Another very interesting flavonoid is quercetin. Its applications are best studied in targeting cancer.…”
Section: Nutraceutical Loaded Nps and Green Npsmentioning
confidence: 99%
See 1 more Smart Citation